Innovations in Manufacturing for Sustainability - Gupta, Kapil; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides details on the innovations made to achieve sustainability in manufacturing. It highlights the trends of current progress in research and development being done to achieve overall sustainability in manufacturing technology. Green-EDM, Hybrid machining, MQL assisted machining, sustainable casting, welding, finishing and casting, energy- and resource-efficient manufacturing are some of the important topics discussed in this book.
Dry and near-dry Machining Techniques for Green Manufacturing -- Cryogenic Machining -- Sustainability issues in Electric Discharge Machining -- Energy Efficient Casting Processes -- Research Framework of Sustainability in Additive Manufacturing -- Sustainability in welding and processing -- Green Machining of Thin Wall Titanium Alloy -- Sustainability Assessment Based Comparative Evaluation of Precision Miniature Gear manufacturing Processes.
Keywords: Sustainability; Surfaces (Technology).; Thin films; Manufactures; Sustainability; Surfaces, Interfaces and Thin Film; Machines, Tools, Processes